Eﬀect of Ba ion on phase formation, microstructure and Photocatalytic Properties of the CuAl2O4 Nanoparticle - Roumaih, Roumaih (European Journal of Applied Sciences, 2021)
The phase purity, microstructure, functional groups, optical and photocatalytic properties were studied for the Cu1-xBaxAl2O4 (x= 0.0, 0.1, and 0.3). The Cu1-xBaxAl2O4 was synthesis by the sol-gel method. The XRD spectra of the parent sample showed a single-phase structure with the space group Fd-3m:2. At x=0.1, the CuAl2O4 structure formed along with CuBaAl10O17, while the BaAl2O4 and CuBaAl10O17 formed at x = 0.3. The analysis of FTIR spectra confirmed the formation of the hexagonal phase structure for x = 0.1 and 0.3. The images of HR-TEM show nanorods along with nanograins for the samples which contain Ba ions. The optical analysis proved the increasing trend in bandgap energy (Eg) with increasing Ba ion doping. The photodegradation was evaluated for the degradation of methylene blue and methyl orange dyes under visible light irradiation. The copper barium aluminate is colored materials so, may be used as a ceramic pigment, also they are useful for humidity sensors application. The novelty of this work, some physical properties of the compound CuBaAl10O17, which is very rarely studied in the literature, will be known.